PENGARUH PENDEKATAN SAVI DALAM METODE EKSPERIMEN TERHADAP PENCAPAIAN KOMPETENSI SISWA PADA PEMBELAJARAN IPA DI SMP NEGERI 1 PADANG - Fanni Fetriasya (PILLAR OF PHYSICS EDUCATION, 2014)
This research motivated by the process of science learning that less attention to ensure the individual differences and learning styles of students, so the potential of the indiviual can’t develop optimally. The learning science includes the science process skills such as observing (visual activity), problem solving (intellectual activity), do the experiment (somatic activity), communicate and asking questions (auditory activity). The students will be remember and understand about the concepts if the teacher involved the students to do the experiment. The teacher can apply student-centered learning approach to convey the material through the explanation, using demonstrations and provide an opportunity to show the performance of the students directly. The approach is known as SAVI approach. This research is include Quasi Experiment. The design of this study is Randomized Control Group Only Design. The population of this research is all the VIII grade students at Junior High School 1 Padang in 2013/2014. The sample was selected by purposive sampling technique. The data of this research is the achievement of competence that include  3 aspects using assessment techniques such as tests for cognitive aspects (form of a written test questions objective) is performed at the end of the study and a non-test for affective and psychomotor aspects (observation sheet). The data analyzed was done by using equality test of two average which use t-test. Based on the analysis of the data, there is a significant impact on the achievement of student competencies SAVI approach to learning by using the experimental method with the real level of 5%